Global imbalances and the lessons of Bretton Woods - Eichengreen, Barry J. (Cairoli lecture series., 2007)
Why the current Bretton Woods-like international financial system, featuring large current account deficits in the center country, the United States, and massive reserve accumulation by the periphery, is not sustainable.